Associations between national plant-based vs animal-based protein supplies and age-specific mortality in human populations - Caitlin J. Andrews; David Raubenheimer; Stephen J. Simpson; Alistair M. Senior (Nature Communications)
Abstract Transitions to sustainable food systems require shifts in food production and availability, particularly the replacement of animal-based protein with plant-based protein. To explore how this transition may relate to demographic patterns, we undertake an ecological analysis of global associations between age-specific mortality, total national macronutrient distributions, and protein substitution. Our dataset includes per capita daily food supply and demographic data for 101 countries from 1961–2018. After adjusting for time, population size, and economic factors, we find associations between low total protein supplies and higher mortality rates across all age groups. Early-life survivorship improves with higher animal-based protein and fat supplies, while later-life survival improves with increased plant-based protein and lower fat supplies. Here, we show that the optimal balance of protein and fat in national food supplies, which correlates with minimal mortality, varies with age, suggesting that reductions in dietary protein, especially from animal sources, may need to be managed with age-specific redistributions to balance health and environmental benefits.